Teori Atom menurut Asy’ariyyah - Hasan Syadzili (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2015)
Al-Asy’ariyyah is one of school of thought in Islam came from the hand of Abu Hasan al-Asy’ari. Asy’ari’s pattern of thought tried to harmonize of both ratio and text implicating the concept of universe as thing constituted from number of atom and accident. This concept had been criticized by several figures. However, al-Asy’ariyyah assert that Allah created something in the way of atom to show His power. In addition, they consistently contend by their ontological view that God’s will is the foundation of the regularity and harmony of this universe. This opinion is important to be known came in the middle of three large school of thought: school of Salafiyah initiated by Imam Ahmad bin Hanbal known by their highly textual method in the making of text as source and instrument to understand Islam; second, school of Islamic philosophy that comprehend aqidah based on ratio as the only source of knowledge; and third, school of Mu’tazilite combine between ratio and text while making ratio as a determinant if the text founded contradict with the rational truth. So al-Asy’ariyyah give a form to their thought dynamically with several features mentioned. According to al-As’ariyyah, the reality of body or thing consists of atom known as al-juz’u alladzi la yatajazza’. This theory is improved later by al-Asy’ariyyah in order to reduce the universe to regular subjectivities which led to God’s will that qadim thus encouraging human to put a faith God as only cause of everything exists. This paper will examine carefully the theory of atom in the view of al-Asy’ariyyah, also present a discussion about the divinity that happen between the mutakallims.